In vitro evaluation of the accuracy of five different electronic apex locators - Nasil Sakkir; Mohamed Asifulla; Vinay Chandra; Mohamed Idris; Shuaib Farooq Razvi; I B Geeta (Wolters Kluwer Medknow Publications, 2015)
Objective of Study: To evaluate in vitro the efficacy of five different electronic apex locators (Root ZX II, i-Root, Endo Master, Triauto ZX, and Elements apex locator) in locating the minor diameter. Materials and Methods: Thirty freshly extracted single-rooted maxillary central incisors were used for the study. Standard access preparation was carried out and the teeth were glued to three plastic frames containing alginate. Electronic working length measurement was determined using all the five apex locators. Following this, the actual canal length was determined by introducing a size 15 K-file into the canal until the tip of the file became visible at the apical foramen under microscope. The mean values of actual length and electronic working length readings were compared using Student t-test and multiple comparison procedures. Results: The average value for actual root canal length was 22.483 ± 1.8731 mm; and the mean electronic root canal length values for Root ZX II, i-Root, Elements, Endo Master, and Triauto ZX apex locators was 22.483 ± 1.7640 mm, 22.400 ± 1.7390 mm, 22.717 ± 1.9462 mm, 22.767 ± 1.9061 mm, and 22.417 ± 1.7523 mm, respectively. P > 0.05 for all the five tested apex locators. Conclusion: All the five modern apex locators tested in this study can determine the working length with high precision and greater predictability.